Tinjauan Literatur Faktor-Faktor yang Mempengaruhi Penggunaan Vape dan Dampaknya terhadap Kesehatan Fisik, Mental, dan Interaksi Sosial Generasi Z - Diyah Nur Muizzah; Risky Akaputra; Andriyani Andriyani (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The dangers of smoking remain a critical issue, with e-cigarette (vape) use rising among Gen Z, often perceived as safer than traditional cigarettes. This study aims to evaluate the factors influencing e-cigarette use among Generation Z and its impacts. Utilizing literature reviews from journals published in the last five years via Google Scholar and PubMate, the research was conducted from March to April 2025. Findings indicate that adolescent behavior is shaped by internal factors like knowledge, confidence, and gender, as well as external factors including parental support, peer influence, and accessibility. To combat the rising e-cigarette use, prevention and promotion efforts are crucial, focusing on education about health risks and strengthening social roles. Ultimately, the goal is to enhance Generation Z's awareness of the risks associated with e-cigarettes.